2018
DOI: 10.1016/j.neuropharm.2018.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine evokes a profile of oxidative stress and impacts innate antiviral response pathways in astrocytes

Abstract: HIV-1 and Zika virus (ZIKV) represent RNA viruses with neurotropic characteristics. Infected individuals suffer neurocognitive disorders aggravated by environmental toxins, including drugs of abuse such as cocaine, exacerbating HIV-associated neurocognitive disorders through a combination of astrogliosis, oxidative stress and innate immune signaling; however, little is known about how cocaine impacts the progression of ZIKV neural perturbations. Impaired innate immune signaling is characterized by weakened ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 112 publications
2
9
0
Order By: Relevance
“…The current study extends these findings by identifying transcriptional deregulation in MND, specifically C/EBPβ and linking its targets to marker genes in astroglia. This may be particularly important as astroglia have been recently implicated in metabolic complications of HAND and AD [48][49][50][51][52][53]. Also consistent with the findings presented here, a recent study showed that YKL-40, a biomarker that reflects astroglial activation, is upregulated in cerebrospinal fluid from HAD cases and is associated with axonal injury [54].…”
Section: Discussionsupporting
confidence: 87%
“…The current study extends these findings by identifying transcriptional deregulation in MND, specifically C/EBPβ and linking its targets to marker genes in astroglia. This may be particularly important as astroglia have been recently implicated in metabolic complications of HAND and AD [48][49][50][51][52][53]. Also consistent with the findings presented here, a recent study showed that YKL-40, a biomarker that reflects astroglial activation, is upregulated in cerebrospinal fluid from HAD cases and is associated with axonal injury [54].…”
Section: Discussionsupporting
confidence: 87%
“…The current study extends these findings by identifying transcriptional deregulation in MND, specifically C/EBPβ and linking its targets to marker genes in astroglia. This may be particularly important as astroglia have been recently implicated in metabolic complications of HAND and AD [49][50][51][52][53][54]. Also, consistent with the findings presented here, a recent study showed that YKL-40, a biomarker that reflects astroglial activation, is upregulated in cerebrospinal fluid from HAD cases and is associated with axonal injury [39].…”
Section: Discussionsupporting
confidence: 87%
“…HIV proteins and ARVs can damage mitochondria, which can generate reactive oxygen species (ROS). 4 , 16 18 HIV proteins can also induce ROS generation as part of the inflammatory response. 19 Thus, persistent low-level HIV protein expression or chronic exposure to ARV likely contributes to long-term exposure to ROS.…”
Section: Discussionmentioning
confidence: 99%
“…HIV proteins and ARV can induce mitochondria to generate ROS as part of the inflammatory response. 17 Recent studies show that astrogliosis and inflammation in AD and in PWH may compromise mitochondrial homeostasis in neurons leading to neurodegeneration, perpetuating ROS-induced inflammation and neurodegeneration. 18 Strategies that disrupt the cycle between oxidative stress, neuroinflammation, and neurodegeneration may be useful in slowing the aging process in PWH on ARVs.…”
Section: Discussionmentioning
confidence: 99%